PENGEMBANGAN ALAT UKUR ACADEMIC HOPELESSNESS INVENTORY : DETEKSI AWAL KEPUTUSASAAN AKADEMIK PADA MAHASISWA - Nathania, Silvia; Audrella, Neisha; Fanesah, Fanesah; D. Frans, Nathanael; Markus Idulfilastri, Rita (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Many students experience low academic achievement and have the potential to cause despair, so early detection is needed through the development of this measuring tool. Low academic grades often cause students to have difficulty in facing various academic challenges. This can cause a sense of despair which will later have an impact on mental health. There is already a measuring tool that measures despair called the Beck Hopelessness Scale (BHS). However, there is no measuring tool that specifically examines despair in the academic field. The purpose of this study is to develop a measuring tool for academic despair for students called the Academic Hopelessness Inventory (AHI). Thus, students who experience obstacles in their college assignments can be detected early. The method used is a quantitative approach with a sample of 377 students, data were collected through a questionnaire that measures student hopelessness in an academic context using a dichotomous scale. The results of the correlation analysis between the Academic Hopelessness Inventory (AHI) and the Beck Hopelessness Scale (BHS) showed a value of r = 1,000 with a significance level of p <0.001. Based on these results, it can be concluded that the Academic Hopelessness Inventory (AHI) and the Beck Hopelessness Scale (BHS) have a strong relationship and measure the same thing. Thus, the Academic Hopelessness Inventory (AHI) measuring instrument can be used to measure the level of academic hopelessness in students. Furthermore, the reliability test of the Academic Hopelessness Inventory (AHI) using the Kuder-Richardson Formula 20 (KR-20) showed 0.946 and the validity test with CFA through the JASP application showed an item value> 0.500. Therefore, the Academic Hopelessness Inventory (AHI) measuring instrument can be used as a measuring instrument for student hopelessness in an academic context. ABSTRAK Banyak mahasiswa yang mengalami rendahnya pencapaian akademik dan berpontensi menimbulkan keputusasaan sehingga diperlukan deteksi awal melalui pengembangan alat ukur ini. Nilai akademik yang rendah sering kali menyebabkan mahasiswa kesulitan dalam menghadapi berbagai tantangan akademik. Hal ini dapat menimbulkan rasa putus asa yang nantinya berdampak pada kesehatan mental. Sudah terdapat alat ukur yang mengukur keputusasaan yang bernama Beck Hoplessness Scale (BHS). Namun, belum terdapat alat ukur yang khusus mengkaji keputusasaan di bidang akademik. Tujuan penelitian adalah mengembangkan alat ukur keputusasaan akademik untuk mahasiswa yang bernama Academic Hopelessness Inventory (AHI). Dengan demikian, mahasiwa yang mengalami hambatan tugas-tugas perkuliahannya dapat dideteksi lebih awal. Metode yang digunakan adalah pendekatan kuantitatif dengan sampel 377 mahasiswa, data dikumpulkan melalui angket yang mengukur keputusasaan mahasiswa dalam konteks akademik menggunakan skala dikotomi. Hasil analisis korelasi antara Academic Hopelessness Inventory (AHI) dan Beck Hopelessness Scale (BHS) menunjukkan nilai r = 1.000 dengan tingkat signifikansi sebesar p < 0.001. Berdasarkan hasil tersebut dapat disimpulkan bahwa Academic Hopelessness Inventory (AHI) dan Beck Hopelessness Scale (BHS) terdapat hubungan kuat dan mengukur hal yang sama. Dengan demikian alat ukur Academic Hopelessness Inventory (AHI) dapat digunakan untuk mengukur tingkat keputusasaan akademik pada mahasiswa. Selanjutnya, uji reliabilitas Academic Hopelessness Inventory (AHI) menggunakan Kuder-Richardson Formula 20 (KR-20) menunjukkan 0.946 serta uji validitas dengan CFA melalui aplikasi JASP menunjukkan nilai butir > 0.500. Maka itu, alat ukur Academic Hopelessness Inventory (AHI) dapat digunakan sebagai alat ukur keputusasan pada mahasiswa dalam konteks akademik.